2019
DOI: 10.1136/rapm-2018-100305
|View full text |Cite|
|
Sign up to set email alerts
|

Hospital safety net burden is associated with increased inpatient mortality and postoperative morbidity after total hip arthroplasty: a retrospective multistate review, 2007–2014

Abstract: BackgroundTotal hip arthroplasty (THA) is one of the most widely performed surgical procedures in the USA. Safety net hospitals, defined as hospitals with a high proportion of cases billed to Medicaid or without insurance, deliver a significant portion of their care to vulnerable populations, but little is known about the effects of a hospital’s safety net burden and its role in healthcare disparities and outcomes following THA. We quantified safety net burden and examined its impact on in-hospital mortality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…La et al found that high safety net burden hospitals were 38% more likely to die after total hip arthroplasty, 11% more likely to develop postoperative complications, and had longer hospital length of stay. 26 Following coronary artery bypass grafting or valvular procedures, SNH has been implicated to have poorer odds of failure to rescue after development of septicemia or tamponade. 15 Persistent demonstration of such adverse findings, even after risk adjustment for patient level characteristics, point to the presence of systemic disparities at SNH, which may serve as barriers to the delivery of high value care.…”
Section: Discussionmentioning
confidence: 99%
“…La et al found that high safety net burden hospitals were 38% more likely to die after total hip arthroplasty, 11% more likely to develop postoperative complications, and had longer hospital length of stay. 26 Following coronary artery bypass grafting or valvular procedures, SNH has been implicated to have poorer odds of failure to rescue after development of septicemia or tamponade. 15 Persistent demonstration of such adverse findings, even after risk adjustment for patient level characteristics, point to the presence of systemic disparities at SNH, which may serve as barriers to the delivery of high value care.…”
Section: Discussionmentioning
confidence: 99%
“…10 Therefore, this cohort tends to be of low socioeconomic status with suboptimally managed medical comorbidities, more housing insecurities, and higher rates of substance abuse. 11 - 14 Additionally, these patients have been shown to experience higher rates of arthritis, 12 worse quality of life while waiting for surgery, 15 longer hospital length of stay (LOS), and more complications after arthroplasty. 13 , 14 , 16 The suspension of arthroplasty procedures, therefore, created a tremendous backlog of arthroplasty patients with neglected and complex deformities, many of whom would be considered high-risk for COVID-19 associated morbidities.…”
Section: Introductionmentioning
confidence: 99%
“… 11 - 14 Additionally, these patients have been shown to experience higher rates of arthritis, 12 worse quality of life while waiting for surgery, 15 longer hospital length of stay (LOS), and more complications after arthroplasty. 13 , 14 , 16 The suspension of arthroplasty procedures, therefore, created a tremendous backlog of arthroplasty patients with neglected and complex deformities, many of whom would be considered high-risk for COVID-19 associated morbidities. 17 Furthermore, as the safety net hospital for the surrounding hospitals, there was an ethical responsibility of caring for all COVID-19 patients who were unable to obtain care elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 Safety net hospitals are defined as those which “by mandate or mission deliver a large amount of care to uninsured and other vulnerable populations.” 16 Unlike other cohorts, patients at safety net county hospitals tend to be of lower socioeconomic status with higher rates of housing insecurities, language disparities, comorbidities, and substance abuse. 17 , 18 Patient cohorts in these safety net hospitals have also been shown to experience higher rates of arthritis, 19 worse quality of life while awaiting surgery, 20 longer hospital LOS, and more complications after TJA. 17 , 18 , 21 Although these disparities create a unique set of challenges, the implementation of a standardized, multidisciplinary RRP could be of notable value in this cohort.…”
mentioning
confidence: 99%
“… 17 , 18 Patient cohorts in these safety net hospitals have also been shown to experience higher rates of arthritis, 19 worse quality of life while awaiting surgery, 20 longer hospital LOS, and more complications after TJA. 17 , 18 , 21 Although these disparities create a unique set of challenges, the implementation of a standardized, multidisciplinary RRP could be of notable value in this cohort.…”
mentioning
confidence: 99%